Proceedings of the International Cross-Disciplinary Conference on Web Accessibility 2012
DOI: 10.1145/2207016.2207049
|View full text |Cite
|
Sign up to set email alerts
|

Mobile sign language translation system for deaf community

Abstract: A BST R A C T Nowadays, web technologies are a very efficient way to ensure communication between a large and heterogeneous audience. Furthermore, web information is mainly based on textual and multimedia content and consequently, some people with special needs, such as deaf and hard of hearing people, have difficulties to access to information or to communicate with hearing people. This problem is due to the lack of services that facilitate sign language learning for hearing people or text translation into si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 7 publications
0
13
0
2
Order By: Relevance
“…In an Australian study, several trials of different communication methods were conducted with deaf (hard of hearing or deaf) participants who mainly used sign language to communicate and it was found that SMS became the most frequently used means of communication when people were given a mobile phone that they had not used before [3].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an Australian study, several trials of different communication methods were conducted with deaf (hard of hearing or deaf) participants who mainly used sign language to communicate and it was found that SMS became the most frequently used means of communication when people were given a mobile phone that they had not used before [3].…”
Section: Resultsmentioning
confidence: 99%
“…conductive and sensorineural hearing loss refers to a combination of injury and a problem that relates both to the external and inner ear [3,4]. Different strategies are useful for communication with person having hearing impairment.…”
Section: Biomedical Research 2018; 29 (5): 1028-1032mentioning
confidence: 99%
“…We illustrate a novel method for transforming an English written text to American Sign Language gloss. This corpus will be useful for statistical analysis for ASL or any related fields [18] [19]. We present the first corpus for ASL gloss that exceeds one hundred million of sentences available for all researches and linguistics.…”
Section: Discussionmentioning
confidence: 99%
“…One of the sign language translation system has been developed for Arabic sign language which can be accessed on mobile devices which translating text into sign language animation [11][12]. In addition to this, there is also a development of sign language translation for learning English sign language [13] and learning Indian sign language [14]. Handheld mobile system has also been created for learning Arabic sign language where users can refer graphic applications to learn sign language [15].…”
Section: Introductionmentioning
confidence: 99%